020 Postural sway as a measure of disease severity in parkinson's disease. Issue 6 (24th May 2018) - Lueck, Christian J; Ilschner, Susanne; Smith, Alex; Vlieger, Robin; Das, Chandi P; Looi, Jeff CL; Apthorp, Deborah
Abstract : Introduction: The severity of Parkinson's disease (PD) is difficult to assess accurately owing to the lack of a robust biological marker of disease progression, with consequent implications for prognosis and treatment. The current standard measure is the Unified Parkinson's Disease Rating Scale (UPDRS) but this is hampered by considerable variability between observers and within subjects. Postural sway correlates well with complex brain functioning in other conditions. This study aimed to investigate the correlation of postural sway with the UPDRS and other non-motor measures of disease severity in patients with PD. Methods: 28 patients with PD (mean age 68 years, range 54–91; 18 male) underwent tests of cognition and quality of life [Montreal Cognitive Assessment (MoCA), Neuropsychiatry Unit Cognitive Assessment (NUCOG) and Parkinson's Diseases Questionnaire (PDQ-39–1)], assessment of postural sway using a force plate, and assessment of clinical status using the motor component of the UPDRS. Results: Sway path length showed strong correlations with PDQ-39–1, MoCA and the verbal fluency component of the NUCOG (r=0.63, –0.75 and −0.57, respectively; p=0.002, <0.001 and 0.002, respectively) and, to a lesser degree, with the UPDRS III (r=0.45, p=0.018). Conclusion: Postural sway shows potential as a sensitive measure of disease severity and brain function in PD, either alone or in combination with other measures. It appears to correlate better with measures of cognition, both general and executive (verbal fluency), and the PDQ measure of disease severity than with the motor component of the UPDRS.